Effects of mind-body interventions on polycystic ovary syndrome: a comprehensive meta-analysis - Kun Zhao; Liuyan Nie; Xiangming Ye; Xiaoyan Hu (BMC, 2024)
Abstract Background Mind-body interventions (MBI) have emerged as a potential therapeutic approach, but their effectiveness in the treatment of Polycystic Ovary Syndrome (PCOS) remains inconclusive. This study systematically evaluates the effectiveness of MBI on quality of life, anthropometry, androgen secretion, glucose, and lipid metabolism in PCOS. Methods A computer search was conducted across three databases: PubMed, the Cochrane Library, and EMBASE, to identify randomized controlled trials (RCTs) related to MBI for PCOS from their inception until July 2024. DerSimonian and Laird's random-effects model and Stata 17.0 software was employed for our meta-analysis. Results Twelve RCTs were included. MBI significantly improved PCOSQ subscale scores, including emotional disturbances (MD: 7.75, 95% CI: 6.10 to 9.40), body hair (MD: 2.73, 95% CI: 0.54 to 4.91), menstrual problems (MD: 3.79, 95% CI: 2.89 to 4.69), and weight (MD: 1.48, 95% CI: 0.03 to 2.93). Furthermore, there was a reduction in depression levels (MD: -1.53, 95% CI: -2.93 to -0.13). Sensitivity analysis confirmed the robustness of PCOSQ-Emotional disturbances and PCOSQ-Menstrual problems, with a high GRADE level of evidence for these subscales. Secondary outcome measures, including waist-hip ratio, fasting blood glucose, and HOMA-IR exhibited statistically significant differences. Subgroup analysis revealed that obesity could influence treatment outcomes. Conclusion MBI can serve as an alternative therapy, modulating effect on the quality of life and depression in PCOS patients. Future well-designed, high-quality, and large-scale studies should be conducted to thoroughly assess the impact of different Mind-Body Interventions (MBI) on various PCOS phenotypes. Trial registration PROSPERO (CRD42023472035).